Toleransi dalam Interdiskursus Teks Sastra dan Teks Non-Sastra - Hilman, Lucia; Tjahjandari, Lily; Untari, Retno (UI Scholars Hub, 2003)
The Indonesian people as a nation consist of a variety of ethnic groups with differentiated culture as well as witch has been planted over such long periods by authorities, has finally exploded coming to the surface in form of various rioting. Should a more in-depth analysis be made then, the actual basic matter to bridge the problem in the existing tolerance for the differences within our multicultural society. An understanding of a certain related tolerance according to François Shanen is expressed in language. As such, literary works and other essays in newspaper with SARA as themes as well as the nation disintegration, forms the corpus of this investigation. From the analysis of the interdiscourse between literary and non-literary texts, it has been conclude that there exists a parallel of thought patterns offered by the literary and non-literary texts against the insight of tolerance in Indonesia, that is violence in the country as caused by there being no tolerance for that which is difference be in differing opinions as to religion, ethnicity or race. Such matter has brought forth the spread of deceptive hatred against religious, racial and certain ethic groups.